Trait mindfulness as a predictive factor for intimate partner violence perpetration among young adults - Horst, Kyle Curtis (Kansas State University, 2013)
Recent literature has highlighted the importance of considering personal and relationship factors in predicting IPV perpetration. The present study sought to investigate whether trait mindfulness is associated with IPV, as well as the mechanisms by which mindfulness might predict IPV. Utilizing longitudinal data collected from 247 undergraduate students, the study tested a hurdle model of IPV occurrence and frequency at Time 3 being predicted by trait mindfulness at Time 1 and other known risk factors at Time 2. Results indicated that trait mindfulness at time 1 was associated with IPV perpetration at Time 3; however, when controlling for other known risk factors at time 1, the association between mindfulness at Time 1 and IPV at Time 3 was no longer significant. Finally, results from the mediational analysis revealed a significant indirect effect of trait mindfulness on IPV through relationship satisfaction and conflict resolution while all variables were measured at the same time point, but no indirect effect of trait mindfulness at time 1 on IPV at time 3.These results indicate that although mindfulness might not be a significant direct predictor of IPV when other known risk factors are controlled for, it is important since mindfulness indirectly predicts IPV through other relationship processes when measured at the same time point. Suggestions for future research and clinical intervention are offered.
Keywords: Mindfulness; Intimate partner violence; Risk factor; Individual & Family Studies (0628)